A Systematic Approach to Domestic Abuse–Informed Child Custody Decision Making in Family Law Cases. (October 2015) - Davis, Gabrielle
<x xml:space="preserve">Abstract</x> This article introduces an approach to domestic violence–informed decision making developed under the auspices of the National Child Custody Differentiation Project, a cooperative undertaking among the Battered Women's Justice Project, the Association of Family & Conciliation Courts, the National Council of Juvenile & Family Court Judges, Praxis International, and the U.S. Department of Justice Office on Violence Against Women. This approach has four essential elements: (1) identifying domestic abuse; (2) understanding the nature and context of domestic abuse; (3) determining the implications of abuse; and (4) accounting for the nature, context, and implications of abuse in all custody‐related recommendations and decisions. Key Points for the Family Court Community: Applying a systematic approach to domestic violence can help practitioners identify, understand, and account for abuse in family law cases. The approach recommended here is suitable for use by anyone who is involved in a contested child custody case at any stage of the proceeding. The specific application of the recommended approach will vary depending upon the practitioner's role and function in the case, relationship to the parties, and access to information, as well as the nature of the proceeding and the issues to be decided.